Islet neogenesis-associated protein signaling in neonatal pancreatic rat islets: Involvement of the cholinergic pathway - Barbosa, Helena C. (2008)
Islet neogenesis associated protein (INGAP) increases islet mass and insulin secretion in neonatal and adult rat islets. In the present study, we measured the short- and long-term effects of INGAP-PP (a pentadecapeptide having the 104-118 amino acid sequence of INGAP) upon islet protein expression and phosphorylation of components of the P13K, MAPK and cholinergic pathways, and on insulin secretion. Short-term exposure of neonatal islets to INGAP-PP (90 s, 5, 15, and 30 min) significantly increased Akt1-Ser473 and MAPK3/1-Thr202/ Tyr204 phosphorylation and INGAP-PP also acutely increased insulin secretion from islets perifused with 2 and 20 mM glucose. Islets cultured for 4 days in the presence of INGAP-PP showed an increased expression of Akt1, Frap1, and Mapk1 mRNAs as well as of the muscarinic M3 receptor subtype, and phospholipase C (PLC)-β2 proteins. These islets also showed increased Akt1 and MAPK3/1 protein phosphorylation. Brief exposure of INGAP-PP-treated islets to carbachol (Cch) significantly increased P70S6K-Thr389 and MAPK3/1 phosphorylation and these islets released more insulin when challenged with Cch that was prevented by the M3 receptor antagonist 4-DAMP, in a concentration-dependent manner. In conclusion, these data indicate that short- and long-term exposure to INGAP-PP significantly affects the expression and the phosphorylation of proteins involved in islet P13K and MAPK signaling pathways. The observations of INGAPP-PP-stimulated up-regulation of cholinergic M3 receptors and PLC- proteins, enhanced P70S6K and MAPK3/1 phosphorylation and Cch-induced insulin secretion suggest a participation of the cholinergic pathway in INGAP-PP-mediated effects.